ANALISIS KEANDALAN KESELAMATAN BANGUNAN TERHADAP BAHAYA KEBAKARAN - Hariyanto Hariyanto (JITEK (Jurnal Ilmiah Teknosains), 2022)
The development of buildings in Blora Regency continues to increase along with the development of the city. Every building has the potential and risk of fire hazard. Fire is one of the disasters that can cause considerable losses. Building safety is a must in a building. Building construction must be balanced with prevention of fire hazards. This prevention must be planned from planning, implementation and post-construction, so that the handling of fire hazards can be applied to the construction itself.The purpose of this study was to determine the weight of priority variables, building safety against fire hazards and the level of reliability in the PEM AKAMIGAS Vyatra VIII Cepu building. The method applied in this study uses the Analytical Hierarchy Process (AHP) method which is effective in helping to solve the problem of the reliability of fire fighting access in buildings, by distributing questionnaires to respondents who work in the construction of the PEM Akamigas Vyatra VIII Building.The results are the reliability of the value system for building fire safety (NKSKB) in the Cepu PEM AKAMIGAS Vyatra VIII building with an assessment of access and water supply for firefighters 13.32%, means of rescue 9.12%, passive protection 8.82%, active protection system 13, 86%. The level of reliability of protection in the PEM AKAMIGAS Vyatra VIII Cepu building is overall "Good" with a percentage of 87.12%. Research on fire risk, both in terms of buildings, occupants and the environment, is expected to be able to reduce and overcome the risk of fire hazards that can occur at any time.